INTERNATIONAL LAW DOCUMENTS - Ahmedov Azimjon; Karimova Odina (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: International Law is complex and specialized field. It is crucial for the elimination of violations of economic, social and cultural rights for international organizations, including international financial institutions, to correct their policies and practices so that they do not result in deprivation of economic, social and cultural rights. This article provides some basic information about International law documents.